Smart verification algorithm for IoT applications using QR tag - Al-Ghaili A.M.; Kasim H.; Rahim F.A.; Ibrahim Z.-A.; Othman M.; Hassan Z. (Springer Verlag, 2023)
Electrical engineering; Mathematical techniques; Brute-force attack; Information leakage; Internet of Things (IOT); QR tag; Security objectives; Smart applications; Unauthorized access; Verification algorithms; Internet of things